Die kerk se regsposisie in Suid-Afrika in die lig van godsdiensvryheid – gereformeerd-kerkregtelik gesien - Smit, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
The Legal Position of the Church in South Africa Regarding Religious Freedom – A Reformed Church Polity Perspective Dissatisfaction with the legal definition of the Church, as voluntary association (societas), bears the potential for creating conflict between Church and State – including for example possible lawsuits concerning topical issues such as “the Church and homosexuality” and the legal position of the clergyman. The core question is: How would an exact view of the Church’s legal position in South Africa regarding religious freedom avert potential conflict between Church and State? The article points out that defining the Church as a voluntary association dates back to the period of the Aufklärung. In Germany, where the Church was originally defined as a voluntary association, the current view of this definition is that it is an abstract and a-historical conception about the Church. Within the framework of it’s legal position, three possible ways of defining the Church are explored. Firstly, the power to define the Church could be ascribed to the State. Secondly, the possibility exists for creating an objective measure for defining the Church. The third possibility, namely that the Church should be entitled to define itself, should be followed in South Africa. The right of the Church to define itself is an essential hallmark of the right of religious freedom in which the legal position of the church should be understood. By virtue of the Church’s self-defining, the State is obliged to accord the Church a status that acknowledges the distinctive position of the Church within the State.